2017
DOI: 10.18388/abp.2016_1416
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of some polyamine derivatives on human prostate and breast cancer cell lines

Abstract: The aim of this study was to expand our knowledge about anticancer activity of some polyamine derivatives with quinoline or chromane as terminal moieties. Tested compounds were evaluated in vitro towards metastatic human prostate adenocarcinoma (PC3), human carcinoma (DU145) and mammary gland adenocarcinoma (MCF7) cell lines. Cell viability was estimated on the basis of mitochondrial metabolic activity using water-soluble tetrazolium WST1 to establish effective concentrations of the tested compounds under expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…IC 50 values for the most active derivative 2a were in the range of 16.8 to 26.6 µM depending on cancer cell line. In addition, 2a induced programed cell death in prostate and breast cancer cell lines by an intrinsic pathway, which involved depolarization of mitochondria together with disruption of its membrane [ 31 , 32 , 33 ]. The design of effective anticancer drugs requires not only the biological activity assessment but also an understanding of the mechanisms involved in the process of eliminating cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IC 50 values for the most active derivative 2a were in the range of 16.8 to 26.6 µM depending on cancer cell line. In addition, 2a induced programed cell death in prostate and breast cancer cell lines by an intrinsic pathway, which involved depolarization of mitochondria together with disruption of its membrane [ 31 , 32 , 33 ]. The design of effective anticancer drugs requires not only the biological activity assessment but also an understanding of the mechanisms involved in the process of eliminating cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 2a induced programed cell death in prostate and breast cancer cell lines by intrinsic pathway, which involved depolarization of mitochondria together with disruption of its membrane [ 31 , 32 , 33 ]. Our studies revealed that anticancer effectiveness of this group of compounds strongly depends on cancer cell line type [ 31 , 32 , 33 ] but these differences may also have their origin in the way the compounds bind to double helix. Therefore, expanding our knowledge about the possible interaction of these compounds with dsDNA or its associated targets such as topoisomerases is of equal importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quinoline compounds can induce and regulate some transcription factors to mediate apoptosis and metabolism, and inhibit the occurrence of cancer and tumors. In addition, quinoline compounds have been confirmed in related studies, which can be effective in inhibiting the development and progression of cancer and tumors …”
Section: Introductionmentioning
confidence: 91%
“…In addition, quinoline compounds have been confirmed in related studies, which can be effective in inhibiting the development and progression of cancer and tumors. [17][18][19][20][21] On the other hand, infectious diseases recently have faced major challenges in the world. The number of people with various plagues and deaths has increased considerably.…”
Section: Introductionmentioning
confidence: 99%